Development of a core design capability for innovative boiling water reactor designs for burning transuranic isotopes using WIMS/PANTHER. (January 2019) - Lindley, B.A.; Tollit, B.; Hino, T; Smith, P.J.; Murgatroyd, J.T.; Smith, P.N.
Highlights: Reactor physics analysis of hard spectrum Resource-renewable BWR (RBWR) designs. Square assembly RBWR-BF ('backfit') with goal of increasing compatibility with ABWR. WIMS/PANTHER model applied to the hexagonal assembly RBWR-TB2 and RBWR-BF. For RBWR-TB2, power shape and reactivity coefficients consistent with previous work. Developed model is fast running and suitable for design studies. Abstract: The resource-renewable boiling water reactor (RBWR) is an innovative BWR design proposed by Hitachi that has the capability to recycle actinides fully, either in a self-sustaining fuel cycle or for the purposes of reducing the environmental impact of long-lived transuranic isotopes (TRUs). Compared to a conventional BWR, a harder neutron spectrum is achieved through utilizing a tight pitch, triangular lattice and increasing the core average void fraction. An axial seed-blanket structure is utilized, with an internal blanket placed between two regions with high TRU loading. In this paper, two TRU-burning configurations of RBWR are considered: the RBWR-TB2, which contains hexagonal assemblies, and the RBWR-BF ('backfit'), which has the goal of increasing the compatibility with existing or planned ABWRs through utilizing the same assembly pitch and shape. A reactor physics modelling capability is developed for these two diverse configurations of RBWR using the UK ANSWERS reactor physics code WIMS and the PANTHER whole core analysis code. The developed models are then applied to the analysis of these RBWR concepts. For the RBWR-TB2, results are consistent with previous work in predicting reactivity coefficients and core power distribution. In particular, the void coefficient is calculated to be negative. WIMS-PANTHER is then applied to the novel case of the RBWR-BF, for which a basic conceptual design is modelled. The void coefficient for the RBWR-BF is calculated to be negative. The developed methodology is relatively fast running and hence is well suited to performing future design studies, in particular for the relatively new concept of the RBWR-BF.